2021
DOI: 10.1007/s40670-021-01263-5
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Blended Learning Approach in the Implementation of a Medical Neuroscience Laboratory Activities

Abstract: Background The COVID-19 pandemic revealed existing gaps in the medical educational system that is heavily dependent on the presence of medical students and teachers in laboratory and class for instruction. This affects continuity in the implementation of the neuroanatomy component of the medical neuroscience laboratory activities during COVID-19. We hypothesized that pivoting wet laboratory neuroanatomy activities to online using an adaptive flexible blended method might represent an effective app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…28,31 Outcomes explored were confidence (n= 5), 21,22,24,25,27 competency (n=2) 20,23 and knowledge (n=6). 26,[28][29][30]32,33 Levels of competency, confidence and knot tying and suturing skills were found to have improved across the course of learning and a further study suggested that levels of competency were the same when learning was conducted virtually (2020) compared to in-person pre-COVID (2019). Evidence from RCTs showed that knowledge was greater when learning was conducted using bespoke interactive platforms with a standard video format reported during the COVID pandemic.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…28,31 Outcomes explored were confidence (n= 5), 21,22,24,25,27 competency (n=2) 20,23 and knowledge (n=6). 26,[28][29][30]32,33 Levels of competency, confidence and knot tying and suturing skills were found to have improved across the course of learning and a further study suggested that levels of competency were the same when learning was conducted virtually (2020) compared to in-person pre-COVID (2019). Evidence from RCTs showed that knowledge was greater when learning was conducted using bespoke interactive platforms with a standard video format reported during the COVID pandemic.…”
Section: Resultsmentioning
confidence: 97%
“…These covered a wide range of both university and clinical based modules/ courses and included neurosurgery, 21 surgical instruments, knot tying and suturing, 24 digital histology, 26 a residency preparation course, 22 simulated patient consultations, documentation, and case presentation, 27 simulated clinical experience in respiratory unit and general medicine, 20 generic medical education, 28 neuroanatomy, 29 emergency medicine 25,33 musculoskeletal system anatomy and neuroanatomy, 30 the National Institutes of Health Stroke Scale, 32 operative techniques and skills, 31 and informed consent for surgical procedures. 23…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations